Alih Kode dalam Video Blog Farida Nurhan pada Youtube - Nadia Yulinda Putri (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2021)
Diversity of languages in Indonesia can lead to language contact events. The emergence of language contact causes several events, one of which is code switching. This study aims to explain and describe the form of code switching and the factors that cause code switching on Farida Nurhan's video blog. The method used in this research is a qualitative method using a sociolinguistic approach. The data in this study are the utterances in five videos belonging to Farida Nurhan on YouTube. The data analysis technique used descriptive qualitative, by connecting the comparison of verbal activities in Farida Nurhan's video blog which was then converted into written form. The results showed that the types of code switching based on context, namely metaphorical code switching and situational code switching, were found but the number was not many. There are 8 metaphorical codes while situational code switching is 2. In the study, it was also found types of code switching based on language, namely internal code switching and external code switching. The form of internal code switching is found: (1) Change of code from Indonesian to Javanese or vice versa is 36, (2) Change of code between varieties, namely formal to informal varieties or vice versa. 13 Indonesian to foreign languages (Arabic and English). Factors that cause code switching were found: (1) Speakers, (2) Opponents of speech, (3) Increase the sense of humor.